The intimate mystery : creating strength and beauty in your marriage - Allender, Dan B.; Longman, Tremper III (Downers Grove, Ill. : IVP Books, 2009)
The book of Genesis provides a matrix for understanding the intimate mystery of marriage in light of three commands-- leave (your family of origin), weave (a life together) and cleave (through sexual intimacy). In this book, Dan Allender and Tremper Longman III explore and unpack the rich implications of this pattern--From publisher description.
Man's best friend--is not a dog -- Meaning of marriage -- Matrix of marriage -- Leaving : making space for faithfulness -- Leaving : walking away from home -- Weaving : connecting communication -- Weaving : bringing our souls together -- Cleaving : united into one flesh -- Cleaving : playing with glory -- In the garden -- Bonus section: the goal of marriage study.
"Now includes six companion Bible studies"--Cover.
Keywords: Marriage -- Religious aspects -- Christianity